Dietary High Dose of Iron Aggravates the Intestinal Injury but Promotes Intestinal Regeneration by Regulating Intestinal Stem Cells Activity in Adult Mice With Dextran Sodium Sulfate-Induced Colitis - Zhang, Yitong; Yin, Lanmei; Zeng, Xianglin; Li, Jun; Yin, Yuebang; Wang, Qiye; Li, Jianzhong; Yang, Huansheng (Frontiers in Veterinary Science, 2022)
The effects of excessive dietary iron intake on the body have been an important topic. The purpose of this study was to investigate the effects of high-dose iron on intestinal damage and regeneration in dextran sodium sulfate (DSS)-induced colitis model mice. Seventy-two 8-week-old adult C57BL/6 mice were randomly divided into 2 dietary treatment groups: the basal diet supplemented with 45 (control) or 450 mg/kg iron (high-iron) from ferrous sulfate. The mice were fed different diets for 2 weeks, and then 2.5% DSS was orally administered to all mice for 7 days. Samples of different tissues were collected on days 0, 3, and 7 post administration (DPA). High-iron treatment significantly decreased the relative weight of the large intestine at 7 DPA but not at 0 DPA or 3 DPA. High dietary iron increased the jejunal villus width at 0 DPA and decreased the villus width, the crypt depth of the jejunum at 3 DPA, and the number of colonic crypts at 7 DPA. Meanwhile, high dietary iron decreased the number of goblet cells in the jejunal villi and the Paneth cells in the jejunal crypts at 0 DPA and increased the number of goblet cells per crypt of the colon at 3 DPA and the number of Paneth cells in the jejunal crypts, the goblet cells in the colon, the Ki67-positive proliferating cells in the colon, and the Sex-determining region Y-box transcription factor 9+ (SOX9) cells in the jejunum crypts and colon at 7 DPA. The organoid formation rate was increased by high-iron treatment at 3 DPA and 7 DPA. High dietary iron treatment decreased the mRNA level of jejunal jagged canonical Notch ligand 2 (Jag-2) at 0 DPA and bone morphogenetic protein 4 (Bmp4) and neural precursor cell-expressed developmentally downregulated 8 (Nedd8) in the jejunum and colon at 7 DPA, whereas it increased the mRNA expression of the serum/glucocorticoid regulated kinase 1 (Sgk1) in the colon at 3 DPA. The results suggested that high dose of iron aggravated intestinal injury but promoted intestinal repair by regulating intestinal epithelial cell renewal and intestinal stem cell activity in adult mice with colitis.